Peningkatan Hasil Belajar Siswa Dengan Menggunakan Media Kartu Truth Or Dare Pada Pembelajaran Matematika Kelas IV SD Pertiwi Makassar Kota Makassar - Nur Rifqayanti Arif; Sukmawati Sukmawati; Ernawati Ernawati (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
The study aims to enhance the learning outcomes of students using Truth or Dare card media on students of 4th grade SD Pertiwi Makassar City of Makassar.This type of research is a Class Action Reaserch that consists of two cycles in which each cycle is performed twice as many meetings. Research procedures include planning, implementation of action, observation and reflection. Subjects in this study are students of the 4th grade SD Pertiwi Makassar City of Makassar of 16 people.The results of the study show that in the first cycle of 16 individual students only 10 students or 63% that meet the criteria of minimum proficiency (KKM) or are in the category sufficient. Classicly already met because of the average score obtained of 75. Whereas in the second cycle where of 16 students there are 14 students or 88% have met the KKM and classically already fulfilled that is an average score gained of 80 or is in the good category. Based on the results of the above research, it can be concluded that the mathematics learning results of students of 4th grade SD Pertiwi Makassar city of Makssar through the media application of Truth or Dare cards have improved